TOWARDS UTILIZATION OF LEAN CANVAS IN THE DEVOPS SOFTWARE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The growth of technology made human to depend more on the software applications in his daily life and nowadays software companies focused more on building robust error free software to end customers in very short time. Software development companies facing one side growth of technological complexity and another side build the products fast to win a competition in business. In recent years growth of a DevOps given lot of new growth opportunity for the software companies.DevOps basic principles focused on the collaboration and communication as a key in between software development information technology professional. It is concentrated on the automating the most of the routine tasks such as development, delivery, infrastructure, support, software testing in software development process. DevOps also emphasize on the building, testing and releasing the software more quickly and in a reliable way.